Preceptor tips for navigating generational differences with introductory and advanced pharmacy practice experience students - Melinda J. Burnworth; Tracy K. Pettinger; Melissa S. Medina; Mary Niemczyk (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Ideally, precepting during introductory and advanced pharmacy practice experiences should be tailored to meet the individualized needs of learners. Understanding generational similarities and differences that exist between both learners and educators will facilitate meaningful interaction and improve learning outcomes. A common pitfall among preceptors is to judge the values of their pharmacy learners based on the stereotypes of the generations. This tends to be more evident when the preceptor's generation differs from the generation of the learner. The following article describes generational attributes that influence experiential learning with general tips for how preceptors can use this information to enhance their interactions with learners. By comparing and contrasting the predominant generations in the current pharmacy education landscape (Baby Boomers, Generation X, and Millennials), the article will demonstrate how multi-generational interactions impact pharmacy education. As Millennials are the majority of experiential learners, the focus will be on their learning preferences and how preceptors can help engage these learners. Practical advice and tools on engaging Millennial learners will be reviewed. Case vignettes will demonstrate how to identify ways to tailor precepting to meet the needs of the learner, avoid common pitfalls, facilitate meaningful interaction, and, ultimately, improve learning outcomes.